Instrumen Evaluasi Bentuk Non- Tes - Iqtianti, Haniefah; Asmara, Nia; Apriyansah, Rizki (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Learning evaluation is not only limited to the cognitive domain that can be measured through written or oral tests but also includes the affective and psychomotor domains, which are more appropriately assessed using non-test instruments. Non-test instruments are evaluation tools used to measure students’ attitudes, interests, motivation, personality, social skills, and behavior. This study aims to describe the concepts, objectives, and types of non-test evaluation instruments relevant to the learning process. The method used is a literature review by analyzing related references. The findings show that non-test instruments include observation, interview, questionnaire, checklist, case study, attitude scale, sociometry, portfolio, teacher’s journal or daily notes, and performance assessment. These instruments play a significant role in providing a comprehensive picture of students’ development, especially in the affective and psychomotor domains. Therefore, the use of non-test instruments complements test-based evaluation to achieve a more holistic and objective assessment in line with educational goals